KARAKTERISTIK KIMIA DAN FISIKA IKAN LELE ASAP DENGAN BAHAN PEMBAKAR BERBEDA (STUDI KASUS UMKM UD SARONA KOTA BINJAI SUMATERA UTARA) - Saqbhani Puspa Sally; Nabila Ukhty; Anhar Rozi; Ikhsanul Khairi (Universitas Teuku Umar, 2019)
Catfish is one of the leading commodities in aquaculture in Indonesia. Catfish derivative products are currently very much developed, one of them was smoked catfish. The characteristics of smoked fish are influenced by several factors, including the type of firewood used. This study aims to examine the chemical and physical characteristics of smoked catfish with different burners. The smoking method used is heat fumigation. The parameters observed were proximate, pH value, phenol content, formaldehyde content, characteristics of color, texture and aroma. The results obtained, protein content, water content, ash content and fat content using laban wood are higher than rambutan wood 60.6%:58.8%; 6.65%:5.54%; 7.97%:7.29%; 20.4%;14.6% repectively. The phenol value of smoked fish using laban wood is higher than that of rambutan wood 0.2401ppm:0.2204ppm respectively. Formaldehyde levels in both types of wood are negative. The characteristics of the two smoked fish are the same in texture, aroma, pH and temperature parameters were solid texture, typical aroma of smoked fish, pH value 6.7 with a temperature of 80-100oC respectively. But the color of smoked fish by burning laban wood is bright brown while the rambutan wood is shiny brown.